Distinct Roles of Tumor Associated Mutations in Collective Cell Migration - Lee, Rachel; Martin, Stuart (University of Dundee, 2021)
Recent evidence suggests that groups of cells are more likely to form clinically dangerous metastatic tumors, emphasizing the importance of understanding mechanisms underlying collective behavior. The emergent collective behavior of migrating cell sheets in vitro has been shown to be disrupted in tumorigenic cells but the connection between this behavior and in vivo tumorigenicity remains unclear. We use particle image velocimetry to measure a multidimensional migration phenotype for genetically defined human breast epithelial cell lines that range in their in vivo behavior from non-tumorigenic to aggressively metastatic. By using cells with controlled mutations, we show that PTEN deletion enhances collective migration, while Ras activation suppresses it, even when combined with PTEN deletion. These opposing effects on collective migration of two mutations that are frequently found in patient tumors could be exploited in the development of novel treatments for metastatic disease. Our methods are based on label-free phase contrast imaging, and thus could easily be applied to patient tumor cells. The short time scales of our approach do not require potentially selective growth, and thus in combination with label-free imaging would allow multidimensional collective migration phenotypes to be utilized in clinical assessments of metastatic potential.
MCF10A, PTEN-/-, KRas, and KRas/PTEN-/- cell lines or the MCF10A and MDA-MB-231 cell lines were plated in a collective migration assay that uses circular cell sheets. Tiled images of each full cell sheet were taken before and after a set of time lapse images was taken of two ROIs in each cell sheet.
Keywords: FOS: Biological sciences; FOS: Biological sciences